Dust acoustic nonlinear periodic waves in a dusty plasma with charge fluctuation - Yadav, L. L.; Singh, S. V.; Bharuthram, R. (My University, 2009)
Using the reductive perturbation method, we present a theory for dust–acoustic nonlinear periodic waves, namely dust–acoustic cnoidal waves, in a plasma containing hot electrons and ions, and warm dust grains with varying charge. It is found that the frequency of the cnoidal wave is a function of its amplitude. It is also found that the dust grain charge fluctuation and other plasma parameters modify the properties of the dust–acoustic cnoidal waves. In the limiting case, these dust–acoustic cnoidal waves reduce to the well-known dust–acoustic solitons.
Keywords: Dusty plasma; Acoustic cnoidal waves; Nonlinear periodic waves